2008
DOI: 10.1016/j.febslet.2008.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Double‐membrane gap junction internalization requires the clathrin‐mediated endocytic machinery

Abstract: Direct cell-cell communication mediated by plasma membrane-spanning gap junction (GJ) channels is vital to all aspects of cellular life. Obviously, GJ intercellular communication (GJIC) requires precise regulation, and it is known that controlled biosynthesis and degradation, and channel opening and closing (gating) are exploited. We discovered that cells internalize GJs in response to various stimuli. Here, we report that GJ internalization is a clathrin-mediated endocytic process that utilizes the vesicle-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 26 publications
(47 reference statements)
6
81
1
Order By: Relevance
“…The latter is consistent with findings by Leithe et al (50) that proteasomal degradation occurs after stimulation of PKC with TPA. Cx43 has been shown to co-localize with clathrin, AP-2, Dab2, and dynamin2 at gap junction plaques (51)(52)(53). Additionally, the loss of dynamin GTPase activity or the reduction of dynamin2, clathrin, AP-2, or Dab2 proteins inhibited the internalization of Cx43, as observed by a significant decrease in the number of annular junctions.…”
Section: Discussionmentioning
confidence: 96%
“…The latter is consistent with findings by Leithe et al (50) that proteasomal degradation occurs after stimulation of PKC with TPA. Cx43 has been shown to co-localize with clathrin, AP-2, Dab2, and dynamin2 at gap junction plaques (51)(52)(53). Additionally, the loss of dynamin GTPase activity or the reduction of dynamin2, clathrin, AP-2, or Dab2 proteins inhibited the internalization of Cx43, as observed by a significant decrease in the number of annular junctions.…”
Section: Discussionmentioning
confidence: 96%
“…The NMR solution structure of WW3 has already been solved albeit in complex with a small peptide (46). All 1 H, 15 N, and 13 C backbone resonances and most side chain and aromatic groups of the WW1 and WW2 domains (97 and 95% of the expected resonances, respectively) were assigned in 1ϫ PBS (pH 7.4) at 25°C (Fig. 1C).…”
Section: Structural Characterization Of the Nedd4 Ww Domains-mentioning
confidence: 99%
“…The rat Nedd4 WW domains WW1 (Nedd4 245-281 ), WW2 (Nedd4 401-437 ), and WW3 (Nedd4 458 -494 ) were cloned into the bacterial expression vector pGEX-KT (GST-tagged; Amersham Biosciences) using standard PCR methods and transformed for overexpression in BL21(DE3) cells (unlabeled, 15 N-, or 13 C, 15 N-labeled) (Agilent Technologies). Purification was conducted as described previously for a recombinant GSTtagged protein with the tag being removed by thrombin digestion (32)(33)(34).…”
Section: Expression and Purification Of Recombinant Proteins And Peptmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofl uorescence (IF) and electron microscopy studies of connexins in endosomal structures (Murray et al, 1981;Naus et al, 1993;Sasaki & Garant, 1986) and IF microscopy evidence of connexins colocalized with endosomal markers such as 54 K. Cochrane et al EEA1, Rab5, and Rab7 (Boassa et al, 2010;Gilleron et al, 2008;Govindarajan et al, 2010;Leithe et al, 2006;Leithe et al, 2009;Segretain et al, 2003) suggest that connexins are internalized from the plasma membrane by endocytic mechanisms. This is also supported by an evidence that the knockdown of proteins required for clathrin-mediated endocytosis such as clathrin, dynamin2, adapter protein complex-2 (AP-2), and Disabled-2 (Dab2) inhibited the internalization of connexin43 (Cx43) (Gilleron et al, 2011;Gumpert et al, 2008;Piehl et al, 2007). Furthermore, it has been shown that gap junctions, which are aggregated in plaques at the plasma membrane, can be internalized into one of the two adjoining cells as unique double-membrane endocytic structures called annular gap junctions (AGJ) or connexosomes (Gumpert et al, 2008;Piehl et al, 2007;Gilleron et al, 2011;Falk et al, 2009).…”
Section: Introductionmentioning
confidence: 54%